The Impact of Blockchain Technology and Dynamic Capabilities on Banks’ Performance - Abayomi Ogunrinde; Carmen De-Pablos-Heredero; José-Luis Montes-Botella; Luis Fernández-Sanz (Big Data and Cognitive Computing)
Blockchain technology has sparked significant interest and is currently being researched by academics and practitioners due to its potential to reduce transaction costs, improve the security of transactions, increase transparency, etc. However, there is still much doubt about its impact, and the technology is still in its infancy, with varying degrees of adoption among different financial institutions. Structural Equation Modeling (SEM) analysis was utilized to test the impact of blockchain and dynamic capabilities on the Bank’s Performance of top banks in Spain. The innovative approach seeks to understand how performance can be improved by deploying blockchain technology (BC) in banks. Results showed a significant association between banks’ adoption of blockchain and the generation of dynamic capabilities and financial performance. Thus, we can confirm that a bank adopting blockchain will more likely create dynamic capabilities than those that do not. Hence, blockchain technology is an important tool for achieving dynamic capabilities and increasing performance in banks. Based on the findings, we suggest areas for additional research and highlight policy considerations related to the wider adoption of blockchain technology.